A Multiplicative Model of Optimal CEO Incentives in Market Equilibrium - Edmans, Alex; Gabaix, Xavier; Landier, Augustin (Review of Financial Studies, 2009)
This paper presents a unified theory of both the level and sensitivity of pay in competitive market equilibrium, by embedding a moral hazard problem into a talent assignment model. By considering multiplicative specifications for the CEO's utility and production functions, we generate a number of different results from traditional additive models. First, both the CEO's low fractional ownership (the Jensen–Murphy incentives measure) and its negative relationship with firm size can be quantitatively reconciled with optimal contracting, and thus need not reflect rent extraction. Second, the dollar change in wealth for a percentage change in firm value, divided by annual pay, is independent of firm size, and therefore a desirable empirical measure of incentives. Third, incentive pay is effective at solving agency problems with multiplicative impacts on firm value, such as strategy choice. However, additive issues such as perk consumption are best addressed through direct monitoring.